2008
DOI: 10.1016/j.vph.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide (NO) and its pathophysiologic regulation

Abstract: Nitric oxide (NO) is a gaseous lipophilic free radical generated by three distinct isoforms of nitric oxide synthases (NOS), type 1 or neuronal (nNOS), type 2 or inducible (iNOS) and type 3 or endothelial NOS (eNOS). Expression of eNOS is altered in many types of cardiovascular disease, such as atherosclerosis, diabetes and hypertension. The ubiquitous chaperone heat shock protein 90 (hsp90) associates with NOS and is important for its proper folding and function. Current studies point toward a therapeutic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
1
26

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 142 publications
(135 reference statements)
9
163
1
26
Order By: Relevance
“…Modulation of eNOS expression and activity affects the outcome of inflammatory vascular diseases (36). Despite the clear contribution of immune responses to these pathologies, the effect of IL-17 on eNOS expression has been poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of eNOS expression and activity affects the outcome of inflammatory vascular diseases (36). Despite the clear contribution of immune responses to these pathologies, the effect of IL-17 on eNOS expression has been poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelially derived NO and its derivatives play critical roles in regulating normal vascular functions but can also be involved in exacerbating or ameliorating cardiovascular diseases (8,10,56,60). For example, NO is a major regulator of angiogenesis and plays important roles in wound healing (53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is generally held that vascular inflammation leads to reduced bioavailability of eNOS-derived NO and eNOS "uncoupling," accompanied by induction of endothelial iNOS expression, which is the source of high, uncontrolled NO that further exacerbates the disease process (10). However, we have found that iNOS activity in inflamed human endothelium can be increased 3-5-fold beyond its basal level by G protein-coupled receptor signaling (11)(12)(13), and accumulating evidence indicates that eNOS could also play an "iNOS"-type role in inflammation, but the mechanisms have not been defined (14).…”
Section: Nos1) Inducible Nos (Inos Nos2) and Endothelial Nos (Enosmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role in the maintenance of small arteries and basal tone of arterioles is supported by experimental observations documenting an increase in blood pressure resulting from the administration of the NOS inhibitor in different animal species (Chatterjee et al 2008).…”
Section: Introductionmentioning
confidence: 91%